The Effectiveness of Using the Interactive Learning Media PeT-Efig (Periodic Table and Electron Configuration) - Safna Anjani; Hairida; Rini Muharini (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the effectiveness of the PeT-Efig interactive multimedia in improving students’ learning outcomes compared to the use of a textbook. The effectiveness was analyzed by comparing the posttest scores of both groups using an independent t-test. The results showed that the Sig. (2-tailed) value was < 0.05, indicating a significant difference between the experimental and control classes. Students who learned using PeT-Efig achieved higher learning outcomes, demonstrating that the media provided a positive impact on conceptual understanding. The effect size calculation produced a Cohen’s d value of 1.3, categorized as a large effect, indicating that the influence of PeT-Efig is very strong and practically meaningful. Overall, this study concludes that the PeT-Efig interactive multimedia is effective as a learning medium because it enhances learning engagement, strengthens information retention, and significantly improves students’ learning outcomes.